Identification of highly penetrant Rb-related synthetic lethal interactions in triple negative breast cancer. Issue 43 (25th October 2018) - Brough, Rachel; Gulati, Aditi; Haider, Syed; Kumar, Rahul; Campbell, James; Knudsen, Erik; Pettitt, Stephen; Ryan, Colm; Lord, Christopher
Abstract Although defects in theRB1 tumour suppressor are one of the more common driver alterations found in triple-negative breast cancer (TNBC), therapeutic approaches that exploit this have not been identified. By integrating molecular profiling data with data from multiple genetic perturbation screens, we identified candidate synthetic lethal (SL) interactions associated withRB1 defects in TNBC. We refined this analysis by identifying the highly penetrant effects, reasoning that these would be more robust in the face of molecular heterogeneity and would represent more promising therapeutic targets. A significant proportion of the highly penetrantRB1 SL effects involved proteins closely associated with RB1 function, suggesting that this might be a defining characteristic. These included nuclear pore complex components associated with the MAD2 spindle checkpoint protein, the kinase and bromodomain containing transcription factor TAF1, and multiple components of the SCFSKP Cullin F box containing complex. Small-molecule inhibition of SCFSKP elicited an increase in p27Kip levels, providing a mechanistic rationale for RB1 SL. Transcript expression of SKP2, a SCFSKP component, was elevated inRB1 -defective TNBCs, suggesting that in these tumours, SKP2 activity might buffer the effects ofRB1 dysfunction.